Entrepreneurial Marketing : Bibliometric Analysis Using Vosviewer - Nuryakin, Nuryakin (SENTRALISASI, 2025)
The study of Entrepreneurial marketing is an important part of the scope of research in the field of marketing and entrepreneurship. A concept of entrepreneurship and marketing that defines business for upcoming difficulties is called entrepreneurial marketing. This study aims to analyze the literature on entrepreneurial marketing. The approach using bibliometric analysis in this study was to measure the development of research on entrepreneurial marketing during the last six years in business and entrepreneurship as well as in the management domain. This study also analyzed research trends and proposed a plan for further studies on entrepreneurial marketing. The research approach merged bibliographic data through extraction from the Scopus database. This study used the bibliometric method on Scopus documents, then screened research articles during 2016-2021. Bibliometric techniques, citation analysis, and co-citation analysis were also used in this study. This study revealed the nature and direction of research carried out by entrepreneurial marketing over the last six years. Seven clusters existed as emerging themes in the entrepreneurial marketing literature. Besides, this study found the most influential authors, journals, institutions, and countries related to research on entrepreneurial marketing with possible future research directions in entrepreneurial marketing